The Role of Perfectionism and Fear of Failure in Predicting the Impostor Phenomenon among Fresh Graduates - Anggraini, Tria; Isnaini, Nurul; Wahyuni, Citra (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Fresh graduate students are in a transition period from the academic world to the working world, a developmental phase often accompanied by increased vulnerability to psychological stress. One form of this stress is the impostor phenomenon, which is the tendency of individuals to doubt their own competence despite having objective evidence of success. This study aims to analyze the influence of perfectionism and fear of failure on the impostor phenomenon in fresh graduate students in Indonesia. This study uses a quantitative approach with a correlational design. Data analysis was conducted using Structural Equation Modeling (SEM). The sampling technique used was non-probability sampling with a purposive sampling method, resulting in 805 participants who met the inclusion criteria and passed the screening process. Data collection was conducted through an online survey using the Clance Impostor Phenomenon Scale (CIPS), the Multidimensional Perfectionism Scale (MPS), and the Indonesian version of the Performance Failure Appraisal Inventory (PFAI). The analysis showed that perfectionism had a positive and significant effect on the impostor phenomenon (β = 0.308; p < 0.01). Fear of failure also proved to have a positive and significant effect (β = 0.471; p < 0.01). Simultaneously, these two variables were able to explain 57.1% of the variance in the impostor phenomenon. These findings indicate that high self-standards and fear of failure play a significant role in the emergence of the impostor phenomenon in fresh graduate students, so that the development of psychological interventions that focus on managing these two factors in the early phase of career transition is needed.Fresh graduate berada pada masa transisi dari dunia akademik menuju dunia kerja, yaitu fase perkembangan yang sering kali disertai dengan meningkatnya kerentanan terhadap tekanan psikologis. Salah satu bentuk tekanan tersebut adalah impostor phenomenon, yaitu kecenderungan individu untuk meragukan kompetensi dirinya meskipun memiliki bukti objektif atas keberhasilannya. Penelitian ini bertujuan untuk menganalisis pengaruh perfectionism dan fear of failure terhadap impostor phenomenon pada fresh graduate di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Analisis data dilakukan menggunakan Structural Equation Modeling (SEM). Teknik sampling yang digunakan adalah non-probability sampling dengan metode purposive sampling, sehingga diperoleh 805 partisipan yang memenuhi kriteria inklusi dan lolos proses screening. Pengumpulan data dilakukan melalui survei daring menggunakan Clance Impostor Phenomenon Scale (CIPS), Multidimensional Perfectionism Scale (MPS), dan Performance Failure Appraisal Inventory (PFAI) versi Indonesia. Hasil analisis menunjukkan bahwa perfectionism berpengaruh positif dan signifikan terhadap impostor phenomenon (β = 0,308; p < 0,01). Fear of failure juga terbukti memiliki pengaruh positif dan signifikan (β = 0,471; p < 0,01). Secara simultan, kedua variabel tersebut mampu menjelaskan 57,1% varians impostor phenomenon. Temuan ini menunjukkan bahwa standar diri yang tinggi dan ketakutan terhadap kegagalan berperan penting dalam munculnya impostor phenomenon pada fresh graduate, sehingga diperlukan pengembangan intervensi psikologis yang berfokus pada pengelolaan kedua faktor tersebut pada fase awal transisi karier.